Environmental stress affects DNA methylation of a CpG rich promoter region of serotonin transporter gene in a nurse cohort. - Jukka S Alasaari; Markus Lagus; Hanna M Ollila; Auli Toivola; Mika Kivimäki; Jussi Vahtera; Erkki Kronholm; Mikko Härmä; Sampsa Puttonen; Tiina Paunio (PLoS ONE)
Background Shift-working nurses are exposed to a stressful work environment, which puts them at an increased risk for burnout and depression. We explored the effect of environmental stress on serotonin transporter gene (SLC6A4) promoter methylation among nurses from high and low work stress environments. Methodology Using bisulfite sequencing, we investigated the methylation status of five CpG residues of a CpG-rich region in the promoter of SLC6A4 by comparing female shift working nurses from a high work stress environment (n = 24) to low work stress environment (n = 25). We also analyzed the association of 5-HTTLPR polymorphism at 5' end of SLC6A4. Work stress was assessed by the Karasek's Model and possible signs of burnout or depression were measured by the Maslach Burnout Index General Survey and Beck Depression Index. Methylation levels were assessed by bisulfite sequencing of DNA extracted from peripheral blood leucocytes. Restriction enzyme treatment followed by standard PCR was used to identify 5-HTTLPR genotypes. Principal findings We found that nurses in the high stress environment had significantly lower promoter methylation levels at all five CpG residues compared to nurses in the low stress environment (p<0.01). There was no significant interaction of 5-HTTLPR genotype and work stress with methylation (p = 0.58). In unadjusted (bivariate) analysis, burnout was not significantly associated to methylation levels. However, when mutually adjusted for both, burnout and work stress were significant contributors (p = 0.038 and p<0.0001 respectively) to methylation levels. Conclusions Our findings show that environmental stress is concurrent with decreased methylation of the SLC6A4 promoter. This may lead to increased transcriptional activity of the gene, increased reuptake of serotonin from synaptic clefts, and termination of the activity of serotonin. This could present a possible coping mechanism for environmental stress in humans that could eventually increase risk for disturbed functional capability and experience of depressed mood in long-term stress.